Historisitas Pengkajian Ilmu Semantik - Maspi Fathurroziq; Satriawan Satriawan (Yayasan Haiah Nusratul Islam, 2026)
This study aims to explain the historical development of semantics scientifically and methodologically, starting from its early emergence in ancient times among philosophers and linguists, through its intermediate stages in Greek and Arab intellectual traditions, until its completion in modern and contemporary linguistic studies. The research focuses on tracing the historical journey of semantics by highlighting the transformation of ideas concerning the relationship between words and meanings, moving from philosophical reflections to scientific studies based on linguistic analysis. Using a descriptive qualitative method with a historical-linguistic approach, this study examines major semantic issues, including types of meaning, semantic field theory, and semantic relations such as synonymy, polysemy, and antonymy. The study concludes that semantics has developed into an essential branch of linguistics that plays a significant role in understanding language, meaning, and communication.